2011
DOI: 10.1074/jbc.m111.260042
|View full text |Cite
|
Sign up to set email alerts
|

Charcot-Marie-Tooth-related Gene GDAP1 Complements Cell Cycle Delay at G2/M Phase in Saccharomyces cerevisiae fis1 Gene-defective Cells

Abstract: Mutations in the GDAP1 gene are responsible of the CharcotMarie-Tooth CMT4A, ARCMT2K, and CMT2K variants. GDAP1 is a mitochondrial outer membrane protein that has been related to the fission pathway of the mitochondrial network dynamics. As mitochondrial dynamics is a conserved process, we reasoned that expressing GDAP1 in Saccharomyces cerevisiae strains defective for genes involved in mitochondrial fission or fusion could increase our knowledge of GDAP1 function. We discovered a consistent relation between F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
0
38
0
3
Order By: Relevance
“…Crystallization of GDAP1 was facilitated by the replacement of the α‐loop (amino acids 145‐200) with a tripeptide GTG‐linker. Limited sequence homology between this region and GSTs had made it difficult to predict a priori whether the α‐loop was an independent domain in between G‐ and H‐sites 16,20,52 or whether it was instead an integral part of the canonical fold. While our structural data do not inform directly on the structure of the α‐loop, helices α4 and α5 in GDAP1 are positioned in a manner similar to most other GSTs, indicating that the α‐loop is an insertion within the H‐site.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallization of GDAP1 was facilitated by the replacement of the α‐loop (amino acids 145‐200) with a tripeptide GTG‐linker. Limited sequence homology between this region and GSTs had made it difficult to predict a priori whether the α‐loop was an independent domain in between G‐ and H‐sites 16,20,52 or whether it was instead an integral part of the canonical fold. While our structural data do not inform directly on the structure of the α‐loop, helices α4 and α5 in GDAP1 are positioned in a manner similar to most other GSTs, indicating that the α‐loop is an insertion within the H‐site.…”
Section: Resultsmentioning
confidence: 99%
“…GDAP1 is a mitochondrial outer membrane protein that has been implicated in mitochondrial fission, although the exact role of GDAP1 in organelle division is less understood than that of Drp1 [72, 73]. Recent studies have reported two cases in which CMT patients carry mutations in both Mfn2 and GDAP1 [74, 75].…”
Section: Neurodegeneration Associated With Altered Mitochondrial Fissmentioning
confidence: 99%
“…At M phase exit, fusion resumes [27,5962]. Furthermore, proteins involved in mitochondrial dynamics, such as Fis1 and GDAP1, have been reported to interact with microtubules, which are integral members in cell division [63]. These fission/fusion processes during the cell cycle become relevant to the disease state when factors such as inflammatory or infectious mediators, ROS/RNS and environmental stimuli alter these processes (e.g.…”
Section: Mitochondrial Fission and Fusionmentioning
confidence: 99%